From Novelty to Pedagogy: The CORE-MR Framework for Mobile Mixed Reality in Elementary Mathematics - Guntur, Mochamad; Sahronih, Siti; Haryanti, Yuyun Dwi; Fitryarany, Della; Munifah, Afra (International Journal of Interactive Mobile Technologies (iJIM), 2026)
Mixed reality (MR) in mathematics education offers the potential to make abstract concepts more concrete and engaging. However, a gap persists between the technological design of MR tools and the complex realities of classroom instruction. This research is urgent because limited studies explain how MR learning designs evolve and support student understanding in practice. Participants included 300 elementary students and 100 teachers in multiple school settings, while a purposive sub-sample of 30 students was selected for in-depth qualitative analysis. The study employed didactical design research (DDR), consisting of prospective, metadidactic, and retrospective stages. Data were collected through classroom observations, semi-structured interviews, and student digital artifacts. Data analysis was conducted using thematic analysis. The findings indicate that MR effectively strengthens spatial reasoning and conceptual understanding of 3D geometry, though some students experienced initial cognitive overload and difficulty transferring visual understanding to symbolic mathematical representations. The implementation also required teachers to shift toward facilitative orchestration of learning activities. The study concludes that DDR enables iterative refinement of MR-based learning designs to better align with authentic classroom needs. This research contributes practical design principles for developing pedagogically grounded MR learning environments.